Light in the East: TimeFrame AD 1000 - 1100 (Alexandria, Virginia, 1988)
This book describes the historical events and the various civilizations that flourished throughout the world, with emphasis on the China's Enlightened Empire, from AD 1000 to 1100.
Keywords: eleventh century